2010
DOI: 10.4049/jimmunol.0901513
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Derived from Hemozoin-Loaded Monocytes Display a Partial Maturation Phenotype that Promotes HIV-1 Trans-Infection of CD4+ T Cells and Virus Replication

Abstract: Coinfection of HIV-1 patients with Plasmodium falciparum, the etiological agent of malaria, results in a raise of viral load and an acceleration of disease progression. The primary objective of this study was to investigate whether the malarial pigment hemozoin (HZ), a heme by-product of hemoglobin digestion by malaria parasites, can affect HIV-1 transmission by monocytes-derived dendritic cells (DCs) to CD4+ T cells when HZ is initially internalized in monocytes before their differentiation in DCs. We demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…The enhancing effect of malaria on DC-mediated trans infection could be due to hemozoin, a pigment that is released in excess after destruction of the infected erythrocytes. The hemozoin-loaded DC are partially activated, leading to increased activation and trans infection of CD4 + T cells [285, 286]. …”
Section: Coinfections and Dc-mediated Hiv-1 Trans Infectionmentioning
confidence: 99%
“…The enhancing effect of malaria on DC-mediated trans infection could be due to hemozoin, a pigment that is released in excess after destruction of the infected erythrocytes. The hemozoin-loaded DC are partially activated, leading to increased activation and trans infection of CD4 + T cells [285, 286]. …”
Section: Coinfections and Dc-mediated Hiv-1 Trans Infectionmentioning
confidence: 99%
“…These semi-mature dendritic cells have a lower surface expression of CCR5 than immature dendritic cells and are less permissive to virus infection. However, these cells exhibit an enhanced transfer of HIV-1 to CD4+ T cells and HIV-1 replication in CD4+ T cells is promoted by contact with these semi-mature, Hz-containing dendritic cells [43]. There does not appear to be a direct effect of Hz on CD4+ T cells [42].…”
Section: Immune Response To Hivmentioning
confidence: 99%
“…Maturation of dendritic cells can readily occur upon most microbial invasion and thus could be a means of increased HIV dissemination in lymphoid tissues during pathogenic co-infection. Recent reports showed that the malarial pigment hemozoin can partially mature DC [22] and activate CD4 þ T cells, leading to a significant enhancement of dendritic cell-mediated transfer of HIV-1 infection [23]. With previous reports, this is another cumulative evidence of the nefarious effect of pathogen co-infection on dendritic cell subversion and HIV spread.…”
Section: Figure 1 Events Involved In Hiv Mucosal Transmission and Virmentioning
confidence: 87%